Change of social status of contemporary women from the Republic of Moldova / Schimbare de statut social la femeile contemporane din Republica Moldova - MIHAI Aurelia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
EcoSoEn Numărul 3-4 / 2022 / ISSN 2587-344X /ISSNe 2587-425X Change of social status of contemporary women from the Republic of Moldova